An Evaluation of a Clinical Care Pathway for the Management of Men With Nonorganic Erectile Dysfunction. Issue 10 (20th August 2019) - Jenkins, Lawrence C.; Hall, Matthew; Deveci, Serkan; Guhring, Patricia; Parker, Marilyn; Nelson, Christian J.; Mulhall, John P.
Abstract: Introduction: There exists little literature on the outcomes of the medical management of men with erectile dysfunction (ED) with no overt organic etiology. Aim: This study was conducted to assess the outcomes of men with nonorganic ED treated medically. Methods: All patients had normal hormone profiles and vascular assessment. All were given a trial of a phosphodiesterase type 5 inhibitor (PDE5i). If no improvement was experienced, intracavernosal injection (ICI) therapy was administered. All patients were encouraged to seek a consultation with a mental health professional. Main Outcome Measure: Patient demographics, medical comorbidities, hormone and hemodynamics assessments, and change in International Index of Erectile Function scores of patients were recorded. Results: 116 men with a mean age or 38 ± 19 (range 16−57) years were studied. 21% had mild ED, 47% had moderate ED, and 32% had severe ED. 21% had seen a psychiatrist. 81% of patients responded to PDE5i with a penetration hardness erection on follow-up (mean duration of 7 ± 3 months postcommencement of PDE5i). However, only 68% of these were capable of a consistently good response. The mean Erectile Function domain score on PDE5i for the entire group improved from 18 ± 11 to 22 ± 6 ( P = .01), and for PDE5i responders it was 27 ± 4 ( P < .001). 28% of men (22 PDE5i failures and 10 with a mixed response to PDE5i) attempted ICI, all obtaining consistently functional erections. At a mean time point of 11 ± 5 months, 83% of those responding to PDE5i had ceased using PDE5i due to a lack of need. 11% of those using ICI continued to use them 6 months after starting ICI; the remainder had been transitioned back to PDE5i. Of the 29 patients in the latter subgroup, 66% were no longer using PDE5i consistently due to a lack of need. Clinical Implications: Not all men with nonorganic ED respond to PDE5i initially and many of those who respond do so only intermittently; such patients are potentially curable, using erectogenic pharmacotherapy for erectile confidence restoration, most men are capable of being weaned from drug therapy. Strengths & Limitations: The strengths of the study are the large number of patients and the use of serial validated instruments to assess erectile function outcomes. As a weakness, despite normal hormone and vascular assessments, the diagnosis of nonorganic ED is still a presumptive one. Conclusion: Medical management of nonorganic ED utilizing the process of care model results in cure in a large proportion of such patients. The transient use of ICI in some patients permits successful PDE5i rechallenge.